A PROSPECTIVE COMPARATIVE STUDY OF STANDARD PCNL VERSUS MINI PCNL FOR THE TREATMENT OF RENAL STONE OF SIZE 10-30 MM. - Kumar, Rakesh; Upadhyay, Rohit; Dheeraj, Kumar; Babelay, Gaurav (Student’s Journal of Health Research Africa, 2024)
Background About 2-3 percent of the general population suffers from urolithiasis. When percutaneous nephrolithotomy (PCNL) was introduced, open surgery was no longer the primary surgical treatment for renal stone disorders. There are currently few studies comparing Mini PCNL to regular PCNL. Furthermore, their relative safety and effectiveness are still up for discussion. Objectives The goal of the study was to compare the effectiveness of Mini PCNL with regular PCNL in treating kidney stones that were between 10 and 30 mm in size. Materials and methods It was a prospective-interventional study. The study took place at the Department of Urology, Indira Gandhi Institute of Medical Sciences (IGIMS), Patna, Bihar, India. The study was conducted for one year, i.e., from November 2021 to December 2022. Results With a p-value of 0.0001, the average decline of hemoglobin in mini PCNL was 0.79 ± 0.37, and in Standard PCNL, it was 1.34 ± 0.84. Both were deemed significant. The average number of days spent in the hospital after surgery was 4.38 ± 1.079 in Mini PCNL and 5.30 ± 1.47 in Standard PCNL, with a p-value of 0.18. The characteristics that were determined after the treatment were stone-free status, the need for ICU, the need for blood transfusion (BT), and fever post-operatively. Conclusion The study concluded that mini PCNL can be considered a safe, acceptable, and effective modality and alternative to Standard PCNL for the treatment of renal calculi of sizes 10-30 mm, resulting in fewer post-op complications, lesser post-op hospital stays, lesser bleeding, and lesser chances of post-op fever and post-op ICU admission. Recommendations A stone-free status should be disclosed to the patient only after post-operative imaging, not based solely on intraoperative results.